Effect of Storage Medium and Aging Duration on Mechanical Properties of Self-Adhesive Resin-Based Cements. Issue 3 (2017) - Liebermann, Anja; Ilie, Nicoleta; Roos, Malgorzata; Stawarczyk, Bogna
Background: The aim of this study was to investigate the effects of storage medium and aging duration on Martens hardness (HM) and indentation modulus (EIT ) of self-adhesive resin-based cements (SARCs). Methods: A total of 416 discs were fabricated from 8 SARCs (n = 52 per SARC): (i) BeautyCem (BEA), (ii) Bifix SE (BIF), (iii) Clearfil SA Cement Automix (CLE), (iv) RelyX Unicem2 Automix (RXU), (v) SeT (SET), (vi) SmartCem 2 (SMC), (vii) SoloCem (SOC) and (viii) SpeedCEM (SPC). The specimens were ground and stored in (a) physiological saliva, (b) artificial saliva, (c) sodium chloride and (d) distilled water, at 37°C for 1, 7, 14, 28, 90 and 180 days. Non-aged specimens (3 hours after photo-initiation) of each SARC acted as control groups. HM and EIT were assessed using a universal hardness testing machine. Data were analyzed using Kolmogorov-Smirnov and Kruskal-Wallis tests and paired t-test, and 3-, 2- and 1-way ANOVA with post hoc Scheffé test (p<0.05). Results: SARC materials exerted the highest influence on HM and EIT values (p<0.001, partial eta squared [ηP ²] = 0.753 and 0.433, respectively), closely followed by aging duration (p<0.001, ηP ² = 0.516 and 0.255) and storage medium (p<0.001, ηP ² = 0.043 and 0.033). The interaction effect of the combinations of the 3 independent parameters was also significant (p<0.001, ηP ² = 0.163 and 0.133). The lowest initial HM and EIT was presented by CLE, followed by SET and SPC; highest HM was for BIF, followed by RXU and SMC. SET gave a greater HM and EIT percentage decrease than SOC, SPC, BEA, SMC, RXU or CLE. Conclusions: Aging duration is a major factor affecting the micromechanical properties of SARCs, while storage medium was shown to have a significant but minor role.